Optical Characterization of Sputter Deposited CdS Thin Films and Measurement of Deposition Rate - Ahamed E.M.K.I.; Das N.K.; Farhad S.F.U.; Khan M.N.I.; Matin M.A.; Amin N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cadmium sulfide; Cadmium telluride; Copper compounds; Deposition rates; Energy gap; II-VI semiconductors; Lime; Magnetron sputtering; Refractive index; Substrates; Sulfur compounds; Thin film solar cells; Tin compounds; Zinc sulfide; Absorption co-efficient; Complex refractive index; Interference fringe pattern; Methodological frameworks; Optical characterization; RF magnetron sputtering technique; Soda lime glass substrate; Transmittance spectra; Thin films